Development of Asynchronous and Synchronous Learning in Bawean Elementary School - Ribeh Najib Muhammad; Riska Widyanita Batubara (Universitas Muhammadiyah Gresik, 2023)
English is one of the most important languages ​​for students, especially at the elementary and middle school levels. Currently, learning activities focus on E-learning. During the COVID19 pandemic, the main focus of teachers is teaching students using learning platforms such as synchronous and asynchronous learning. Synchronous learning here focuses on the Zoom and asynchronous platforms using video material. The researcher used two strategies to measure which strategy was more effective to assist students in facilitating the E-learning learning process. The process also aims to reach students and teach them from home during quarantine. This service proposal tries to improve the quality of e-learning learning materials using synchronous (zoom) and asynchronous (video materials), at a Thai Elementary School. The students have experience during the COVID-19 pandemic quarantine period using e-learning. Learning English including e-learning is needed to improve four language skills, including listening, speaking, reading, and writing. In learning English students can use an easy alternative by utilizing technology.